Atmospheric CO2 forcing on Mediterranean biomes during the past 500 kyrs - Koutsodendris, Andreas; Dakos, Vasilis; Fletcher, William J.; Knipping, Maria; Kotthoff, Ulrich; Milner, Alice M.; Müller, Ulrich C.; Kaboth-Bahr, Stefanie; Kern, Oliver A.; Kolb, Laurin; Vakhrameeva, Polina; Wulf, Sabine; et al. (Nature Communications, 2023)
There is growing concern on the survival of Mediterranean forests under the projected near-future droughts as a result of anthropogenic climate change. Here we determine the resilience of Mediterranean forests across the entire range of climatic boundary conditions realized during the past 500 kyrs based on continuous pollen and geochemical records of (sub)centennial-scale resolution from drillcores from Tenaghi Philippon, Greece. Using convergent cross-mapping we provide empirical confirmation that global atmospheric carbon dioxide (CO2) may affect Mediterranean vegetation through forcing on moisture availability. Our analysis documents two stable vegetation regimes across the wide range of CO2 and moisture levels realized during the past four glacial-interglacial cycles, with abrupt shifts from forest to steppe biomes occurring when a threshold in precipitation is crossed. Our approach highlights that a CO2-driven moisture decrease in the near future may bear an impending risk for abrupt vegetation regime shifts prompting forest loss in the Mediterranean region.
Gesehen am 09.08.2023